Analisis Vegetasi Gulma pada Kebun Kopi Arabika (Coffea arabica L.) di Balingka, Agam, Sumatera Barat - Indah Prafitri Yussa; Chairul Mahmud; Zuhri Syam (Jurnal Biologi Universitas Andalas, 2015)
The vegetation analysis of weed from Coffee Arabica (Coffea arabica L.) traditional farm in Balingka, Agam has been conducted from February to May 2014. The purpose of this study was to determine the composition and structure of weed on the farm. Vegetation was sampled systematically using square plot (1x1 m2) with a total 32 plots. The results found that composition of the weed in the farm were 11 families, 21 genera and 25 species. A total number of individuals were 3114. Borreria laevis dominated at the coffee farm with the highest SDR (Summed Dominance Ratio) (22.809%). Diversity index (H') of the weed in coffee farm was 2.04. Keywords: weed, Coffea arabica L., composition, structure